Obsceno, paródia e grotesco em Bufólicas de Hilda Hilst - Rocha, Carlos Alexandre da Silva (2014)
In Bufólicas, 1992, the last book that composes the obscene tetralogy of Hilda Hilst - also incorporated by O caderno rosa de Lori Lamby, 1990; Contos d’escárnio & textos grotescos, 1990; and Cartas de um sedutor, 1991 –, from the obscene, the author, denudes and exposes political “defects” and conservative behavior. As warned by the critic and organizer of Hilst’s work, Alcir Pecora (2005), the concept of obscenity is present in the book and whole work of the author, as the obscene is perceived in the use of words that make reference to the excretory organs sexually used. Thus, this research is focused on the last book of the tetralogy, in which there is, besides the obscene, the grotesque realism, studied by Mikhail Bakhtin ([1965] 1993), in which one perceives the use of opposites and of the lower regions of the body from where laugh and criticism arise. In the seven fable-poems that compose Bufólicas are present traditional characters of fairy tales, as the king, the queen, the witch, the girl, the wolf, the grandmother, the dwarf, the fairy and the maiden. These characters, related either with the good, sometimes with the evil, are commonly linked to the higher region of the body; however, in the seven poems they appear with sexual related emotions, being thereby, incorporated into lower region of the body, to the reproductive and excretory regions. We see, therefore, the union of disparate elements in the composition of poems that mix genres and high registers with the low ones, as fairy tales and fables with the grotesque and obscene that demean this classic literature to the ground floor. In this sense, this work aims to analyze the obscenity in this fable-poems, relating them to the notions of the grotesque and parody, focusing reflections on the subject, besides those already mentioned, Georges Bataille ([1957] 2013), Wolfgang Kaiser ([1957] 1986), Victor Manuel de Aguiar e Silva ([1967] 2007), Vladimir Propp ([1976] 1992), Linda Hutcheon ([1984] 1985) and Sarane Alexandrian ([1989] 1994). It will analyze the seven fable-poems Bufólicas, bringing them closer to their respective character models in fairy tales, in order to investigate the effect of this parodic, grotesque and obscene literary approach.